Penelitian Stainless Steel 202 Terhadap Pengaruh Pengelasan Gas Tungsten Arc Welding (Gtaw) Untuk Variasi Arus 50 A, 100 A dan 160 A dengan Uji Komposisi Kimia, Uji Struktur Micro, Uji Kekerasan dan Uji Impact - Trianto, Agus; , Ir. Pramuko Ilmu Purboputro, MT (2016)
The purpose of this study was to determine the percentage of the chemical composition of the stainless steel 202 and microstructure , hardness price , price impack stainless steel welds 202 to variations in air and water cooling. The materials studied are stainless steel AISI 202. The welding test specimen with current variation and cooling is done with water and air . Tests were conducted: Chemical composition testing ( Optical Emission Spectrometer ) , testing microstructure ( Ulympus Metallurgical Microscope and Photomicrographic System) , hardness testing ( Vickers Hardness ) and impact testing ( ASTM 23 , Type A) The test results are known chemical composition of the material type of austenitic stainless steel alloy Fe - Cr - Ni , levels of iron ( Fe ) = 72.6 % , chromium ( Cr ) = 17.6 % , nickel ( Ni ) = 4.01 % , and manganese ( Mn ) = 10.0 % , micro .Struktur didaapatkan austenite phase , ferrite and chromium carbides . 50 A specimen flow of air conditioning , air conditioning currents of 100 A , current 50 A water cooler and flows 160 a cooling water rather coarse grain structure and more chromium carbides . A flow of 160 specimens obtained air conditioning grain structure of the rudest and most forms chromium carbide . Hardness testing obtained an average price of violence lowest specimen on the specimen current of 100 A water cooler : welding